Therapeutic effects of Pueraria lobata (Willd.) Ohwi root and Hovenia dulcis Thunb. extracts on alcoholic liver disease: Network pharmacology and experimental validation - Zhendong Chen; Yu Yue; Hongyan An; Haisu Yan; Hyeok-Joo Park; Pei Lin (Journal of Traditional Chinese Medical Sciences)
Objective: To investigate the protective effects of the combined concentrated liquid extract of Pueraria lobata (Willd.) Ohwi root (P. lobata, Ge Gen) and Hovenia dulcis Thunb. (H. dulcis, Zhi Ju Zi) against ethanol-induced liver damage in vitro, using a human hepatoma cell line G2 (HepG2) cell model. Methods: HepG2 cells were cultured in medium containing 4% ethanol to establish a model of alcoholic liver damage. The cells were then treated with the combined extract obtained via cryogenic extraction. Biochemical assays and Western blot analyses were performed to assess the levels of oxidative stress markers, antioxidant enzymes, and inflammatory cytokines. In addition, activation of the phosphoinositide 3-kinase/protein kinase B (PI3K/AKT) pathway was examined to elucidate the mechanisms underlying the effects of the extract. Results: Treatment with the extract contributed to a significant reduction in the release of nitric oxide and reactive oxygen species in the ethanol-treated HepG2 cells; promoted the elevated expression of superoxide dismutase, catalase, and glutathione, indicating enhanced antioxidant defenses; and showed strong free radical-scavenging activity against 1,1-diphenyl-2-picrylhydrazyl radicals. In addition, by activating the PI3K/AKT pathway, treatment promoted increases in the expression of nuclear factor erythroid 2-related factor 2 and its downstream targets, subsequently inhibiting apoptosis. Moreover. inflammatory responses were mitigated, as indicated by reductions in the expression of tumor necrosis factor-alpha and interleukin-6, and we detected reduction in the levels of alanine aminotransferase and aspartate aminotransferase, thereby indicating hepatoprotective effects. Conclusion: The combined P. lobata root and H. dulcis extract was established to have notable antioxidative and anti-inflammatory properties, effectively alleviating ethanol-induced liver damage in vitro. These findings highlight the potential applicability of this extract as a candidate for treating alcoholic liver disease.